Monstrosität : Abweichungen in Literatur und Wissenschaften des 19. Jahrhunderts - Howe, Jan Niklas (WeltLiteraturen / World Literatures., 2016)
"The study examines the parallel emergence of a new paradigm of deviation in literature and science. From Hoffmann and Poe to Henry James, from medical teratology and early psychiatry to the theory of evolution, the book traces the development of a modern dialectic of the defiguration and refiguration of monstrous forms."--